The storyteller : a novel - Picoult, Jodi, 1966- (New York Atria, 2013)
Becoming friends with Josef Weber, an old man who is particularly loved in her community, Sage Singer is shocked when one day he asks her to kill him and reveals why he deserves to die, causing her to question her beliefs.
Includes bibliographical references.
Keywords: Bakers -- Fiction; Friendship -- Fiction; Good and evil -- Fiction; Ex-Nazis -- Fiction; Psychological fiction. 85 holds on first copy returned of 31 copies LOCATION CALL NO. STATUS APL New Fiction FIC Picoult, J. DUE 03-13-13 APL New Fiction FIC Picoult, J. c.2 ON HOLDSHELF APL New Fiction FIC Picoult, J. c.3 ON HOLDSHELF Belfast New Books FIC PIC ON HOLDSHELF Camden PL New Fiction F Pic DUE 03-13-13 CML Adult Fiction NEW FIC Picoult J ON HOLDSHELF CML Adult Fiction NEW FIC Picoult J c.2 DUE 03-19-13 CML Adult Fiction NEW FIC Picoult J c.3 ON HOLDSHELF CML Adult Fiction NEW FIC Picoult J c.4 DUE 03-19-13 Edythe Dyer New Adult Fic Picoult J DUE 03-20-13